Analysis of Salivary Neuropeptides in Anxiety and Depression Using the Luminex MAGPIX® System - Kupcova, Ida; Danisovic, Lubos; Bernatova, Sona; Harsanyi, Stefan (Curēus, 2024)
BACKGROUND: Anxiety and depressive disorders are highly prevalent mental health conditions, affecting millions worldwide. Advancements in neurobiology have identified the effects of various neuropeptides in modulating mood and stress responses. Some of the well-researched neuropeptides in plasma are oxytocin (OXT), alpha-melanocyte-stimulating hormone (alpha-MSH), beta-endorphin, neurotensin, and substance P. In this study, we used methods of liquid biopsy to acquire saliva samples to analyze the concentrations of neuropeptides associated with depression. METHODS: The study was conducted in Bratislava, Slovakia, from January to June 2022. Participants were 20 subjects treated for depression and anxiety without medication; the control group consisted of 20 healthy individuals with no personal history of depression or anxiety. Salivary samples were collected using buccal swabs to measure the concentrations of the examined neuropeptides. Laboratory analysis was based on detecting fluorescent signals performed on the Luminex MAGPIX® System (Luminex Corporation, Austin, Texas). Means and standard deviations were calculated for individual neuropeptide levels. To determine if there are statistically significant differences in neuropeptide levels between individuals with and without depression, independent t-tests and a one-way ANOVA were conducted. RESULTS: Our findings indicate a significant decrease in all studied neuropeptides in subjects compared to healthy controls. Reductions in mean levels were observed for OXT (7.3), alpha-MSH (3.9), beta-endorphin (2.9), neurotensin (15.1), and a 6.9-fold decrease for substance P. Alpha-MSH and beta-endorphin showed higher variability in measured levels within both groups. CONCLUSION: The results of this study indicate that the levels of the studied salivary neuropeptides, OXT, alpha-MSH, beta-endorphin, neurotensin, and substance P, are statistically significantly reduced in individuals with depression compared to healthy controls.